Research on localization scheme of UWB in NLOS environment - XIAO Zhu1; YU Quan2; YI Ke-chu1; WANG Yong-chao1 (Tongxin xuebao)
A localization scheme via UWB suitable for NLOS was given and a TOA estimation based on the strongest path （SP） detection was proposed. The positioning operation between FS and MT was implemented when FS detected two strongest paths from different direction. The aforementioned scheme was also applicable for LOS situation and it was unnecessary to consider the location of obstruction. According to three NLOS channel model simulations in IEEE.802.15.4a,the relationship between channel impulse response and SP search region was analyzed,localization per-formance impacted by various parameters was also discussed. The results demonstrate the feasibility and validity of the proposed scheme especially when is unable to detect the direct path in NLOS.